KEDUDUKAN HUKUM NOTARIS DALAM PENCEGAHAN PENGGUNAAN HASIL KORUPSI DALAM PEMBENTUKAN PERUSAHAAN - Hastarini, Arvita (UNES Law Review, 2023)
The reduced central supervision of the regions causes budgetary and authority deviations so that they tend to commit acts of corruption. Various methods were used to hide the money resulting from corruption, one of which was by placing the funds in a company. Through normative juridical research, it is found that notaries can play a role in preventing money laundering by reporting perpetrators who are suspected of committing money laundering crimes even though the Notary Office Law requires Notaries to keep everything confidential regarding the deed, unless the Law stipulates other. The legal position of a Notary, apart from being a public official (openbaar ambtenaar) who is authorized to make authentic deeds, can be held responsible for his actions in connection with his work in making deeds and is obliged to keep the contents of the deed secret, but also a Notary as part of law enforcement officials and citizens of Indonesia. who comply with the law according to government regulation Number 43 of 2015 is one of the parties that is obliged to report a party suspected of having committed a crime of money laundering.